Epworth League Institute at Feather River - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of attendees of the Epworth League Conference at Feather River. Some attendees hold banners indicating a locality or organization they identify with, these include the following: "Napa," "St. Stephens Oakland," "Petaluma," "Santa Clara Ave." "Rio Linda," "Epworth," and "Chico."